Studi Kejadian 2:4b-3:24 dengan konsep naratologi Tzvetan Todorov - Setiawan, Yohanes; Sin, Sia Kok (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This study aims to analyze the narrative of Genesis 2:4 b-3:24 using Tzvetan Todorov's narratology theory, which consists of five phases: equilibrium, disruption, recognition, repair, and new equilibrium. This study uses a descriptive-qualitative approach to reveal the socio-theological aspects present in the text. The findings show that the narrative structure reflects a cycle of harmony and conflict, starting with the initial equilibrium of the relationship between God, humans, and creation. Disruption occurs through the serpent's temptation, which leads to human transgression and subsequent acts of recognition. The narrative continues to repair, where consequences are imposed, and finally reaches a new equilibrium that illustrates God's justice and mercy in providing a new beginning for humans. This analysis not only enhances the understanding of the socio-theological implications of the text but also invites a re-evaluation of traditional interpretations of humanity's expulsion from Eden and the ongoing relationship between society, creation, and God. Abstrak Penelitian ini bertujuan untuk menganalisis narasi Kejadian 2:4 b-3:24 menggunakan teori naratologi Tzvetan Todorov, yang terdiri dari lima fase: equilibrium, disruption, recognition, repair, dan new equilibrium. Penelitian ini menggunakan pendekatan deskriptif-kualitatif untuk mengungkap aspek sosial-teologis yang ada dalam teks. Temuan menunjukkan bahwa struktur narasi mencerminkan siklus harmoni dan konflik, dimulai dengan equilibrium awal hubungan antara Tuhan, manusia, dan ciptaan. Disruption terjadi melalui godaan ular, yang mengarah pada pelanggaran manusia dan selanjutnya ada aksi recognition. Narasi berlanjut ke repair, di mana konsekuensi dipaksakan, dan akhirnya mencapai new equilibrium yang menggambarkan keadilan dan belas kasihan Tuhan dalam memberikan awal yang baru bagi manusia. Analisis ini tidak hanya meningkatkan pemahaman tentang implikasi sosial-teologis dari teks tetapi juga mengundang evaluasi ulang terhadap interpretasi tradisional mengenai pengusiran manusia dari Eden dan hubungan yang berkelanjutan antara umat manusia, ciptaan dan Tuhan.